2023
DOI: 10.1055/s-0043-1767816
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum Opioid Prescribing in Patients with Opioid Use Prior to Birth

Abstract: Objective This study aimed to describe opioid prescribing patterns for pregnant patients with a history of or active opioid use to inform postpartum pain management strategies. Study Design We conducted a retrospective cohort analysis of all patients with a history of opioid use disorder (OUD) or chronic pain seen at a single outpatient clinic specializing in opioid use and OUD in pregnancy from January 2019 to August 2021. Patient characteristics, delivery outcomes, and opioid prescribing informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Additionally, one study found that receipt of an opioid prescription in the three months prior to delivery was associated with an increased likelihood of MOUD discontinuation compared to without a prenatal opioid prescription [4]. Another recent study found that opioid refill rates for post-delivery pain were increased in patients with OUD or chronic pain compared to individuals without these diagnoses [8]. On the other hand, one study found that experiences of self-reported pain are associated with recurrence of non-prescribed opioid use among individuals with OUD [9].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, one study found that receipt of an opioid prescription in the three months prior to delivery was associated with an increased likelihood of MOUD discontinuation compared to without a prenatal opioid prescription [4]. Another recent study found that opioid refill rates for post-delivery pain were increased in patients with OUD or chronic pain compared to individuals without these diagnoses [8]. On the other hand, one study found that experiences of self-reported pain are associated with recurrence of non-prescribed opioid use among individuals with OUD [9].…”
Section: Introductionmentioning
confidence: 99%